LOMBA PERANCANGAN POSTER DIGITAL SEBAGAI MEDIA SOSIALISASI HEMAT ENERGI DI SMK ISLAM PERTI TOMANG - Joni Fat; Endah Setyaningsih; Yohanes Calvinus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Energy saving is one of the most dominant issues in the current era because of the massive use of energy in various fields. Therefore, in this Community Service (PkM) activity, energy saving is used as the central topic. In this PkM activity, Perti Tomang Islamic Vocational School students made digital posters for energy-saving socialization both in their environment and online through social media. The topic of energy saving raised is not limited to saving in the field of lighting (this is a topic taken in Pkm Dikti activities), but also various types of energy savings that can be done such as savings in the use of household appliances, savings in schools, savings in the use of equipment electronics, and others. This poster was judged by the Jury based on the provisions, namely the number of likes, the suitability of the design with the theme and the content of the message conveyed. The Jury Team chose the winners for the categories of Favorite Islamic Vocational School Teacher Perti, Favorite Social Media, and Best Design. For the Favorite Teacher category, the first winner is a student named Rosyid, the second winner is Amanda Ayodhya and the third winner is Ade Alfiano. In the Social Media category, first place is Melda Amelia, second place is Meylani, and third winner is Fitri Nur Luiana. In the Best Design category, the first place winner is M. Maksum, the second winner is M. Arya Dilla and the third winner is Nina Safridah. The event was all conducted online due to the current limitations, namely the Covid-19 pandemic. With the procurement of this activity, it is hoped that in addition to introducing the energy lifestyle to students, it is also possible to introduce the Electrical Engineering study program more. Hemat energi merupakan salah satu isu paling dominan dalam era saat ini karena masifnya penggunaan energi dalam berbagai bidang. Oleh karena itu, dalam kegiatan Pengabdian kepada Masyarakat (PkM) yang diadakan ini, hemat energi digunakan sebagai topik sentral. Pada kegiatan PkM ini, para siswa SMK Islam Perti Tomang membuat poster digital untuk sosialisasi hemat energi baik di lingkungannya mau pun secara daring melalui media sosial. Topik hemat energi yang diangkat tidak terbatas pada penghematan di bidang pencahayaan (ini merupakan topik yang diambil dalam kegiatan Pkm Dikti), tetapi juga boleh berbagai jenis penghematan energi yang dapat dilakukan seperti penghematan dalam pemakaian peralatan rumah tangga, penghematan di sekolah, penghematan dalam pemakaian peralatan elektronika, dan lain-lain. Poster ini dinilai oleh Tim Juri berdasarkan ketentuan, yaitu jumlah like, kesesuaian rancangan dengan tema dan isi pesan yang disampaikan. Tim Juri memilih juara untuk kategori Favorit Guru SMK Islam Perti, Favorit Media Sosial, dan Best Design. Untuk kategori Favorit Guru, Juara I adalah siswa dengan nama Rosyid, Juara II Amanda Ayodhya dan Juara III Ade Alfiano. Kategori Media Sosial, Juara I Melda Amelia, Juara II Meylani, Juara III Fitri Nur Luiana. Kategori Best Design, Juara I adalah M. Maksum, Juara II M. Arya Dilla dan Juara III Nina Safridah. Acara semuanya dilakukan secara daring karena keterbatasan kondisi saat ini, yaitu pandemi Covid-19. Dengan pengadaan kegiatan ini, diharapkan selain dapat memperkenalkan pola hidup energi kepada para siswa juga dapat lebih mengenalkan program studi Teknik Elektro.